Role of superoxide radical and singlet oxygen in peroxymonosulfate activation by iron-doped bone char for efficient acetaminophen degradation - Zeng, Yifeng; Wang, Fan; He, Dongqin; Sun, Jianqiang; Li, Jun; Luo, Hongwei; Pan, Xiangliang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Iron was doped into swine bone-derived biochar via a simple method.•Iron-doped bone char was first involved in peroxymonosulfate activation system.•The active site of iron-doped bone char was explored.•The generation mechanism of reactive oxygen species was elucidated. Bone char is a hydroxyapatite-rich product obtained by calcining animal bones. However, the role of inorganic hydroxyapatite is often overlooked in bone char-catalyzed persulfate systems. In this work, iron was doped into swine bone-derived biochar (Fe-BC) by simple impregnation, and the Fe-BC catalysts were used for the first time to activate peroxymonosulfate (PMS). The obtained Fe-BC/PMS system could rapidly degrade the target pollutants (0.0529 s−1, 90 s) employing singlet oxygen (1O2) as the dominant reactive oxygen species (ROS). The characterization results demonstrated that iron was mainly intercalated into the catalyst by substituting calcium sites in swine bone biochar, and the Fe-BC composition was significantly affected by annealing temperature. A comprehensive study including quenching experiments, electron paramagnetic resonance (EPR), chemical probes, and linear sweep voltammetry (LSV) revealed that 1O2 was the dominant ROS. According to the characterization results, 1O2 was generated from the conversion of superoxide radical (O2•−) and the self-dissociation of PMS. Iron was the main active site of Fe-BC catalysts, and the carbon defects and oxygen-containing groups also played roles in catalyzing PMS. The Fe-BC/PMS system exhibited outstanding oxidative capability over a wide pH range (3.0–9.0) and was resistant to interference from some high concentrations of anions (Cl−, NO3–, and SO42−). This work provides a new perspective on using animal bone-derived biochar catalysts in advanced oxidation processes.